God is my inheritance: The voice of the woman in Psalm 16 - Barus, Armand (Verbum et ecclesia, 2023)
Differing with most scholars Psalm 16 was a personal lament Psalm voiced by a woman, with the central theme being, God is the portion of my inheritance. The concluding statement was revealed to us through the use of poetic criticism on Psalm 16. Poetic criticism is a new method of reading lament Psalms through the careful observation of elements contained in the lament Psalms, such as lament, feeling, the concept of God and mood of the text. The application of poetic criticism on Psalm 16 by studying the elements of the lament, feeling, concept of God, and changes of mood, has shown us that the psalmist successfully faced the struggles of life when she lost her husband and as a result, her inheritance, because God is her inheritance. In and through her suffering the psalmist was able to know God as her portion of inheritance. Intradisciplinary and/or interdisciplinary implications: This research helps the readers understand the involvement of women in arranging the Psalms in the spiritual lives of Israel and Psalms can be studied now from feminist perspective.